2012
DOI: 10.4269/ajtmh.2012.11-0715
|View full text |Cite
|
Sign up to set email alerts
|

Boiling as Household Water Treatment in Cambodia: A Longitudinal Study of Boiling Practice and Microbiological Effectiveness

Abstract: Abstract. This paper focuses on the consistency of use and microbiological effectiveness of boiling as it is practiced in one study site in peri-urban Cambodia. We followed 60 randomly selected households in Kandal Province over 6 months to collect longitudinal data on water boiling practices and effectiveness in reducing Escherichia coli in household drinking water. Despite 90% of households reporting that they used boiling as a means of drinking water treatment, an average of only 31% of households had boile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 24 publications
7
46
1
Order By: Relevance
“…In this study, reported boiling was associated with a significant reduction in contamination of stored water among households with contaminated source water, a finding that is consistent with other research. [31][32][33][34][35][36] In some studies, however, reported boiling has been associated with no effect 37,38 or even an increase in contamination. 39 Because there is no objective measure of boiling, assessment relies on self-report, which may substantially overestimate actual practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, reported boiling was associated with a significant reduction in contamination of stored water among households with contaminated source water, a finding that is consistent with other research. [31][32][33][34][35][36] In some studies, however, reported boiling has been associated with no effect 37,38 or even an increase in contamination. 39 Because there is no objective measure of boiling, assessment relies on self-report, which may substantially overestimate actual practice.…”
Section: Discussionmentioning
confidence: 99%
“…All these options significantly reduce E. coli concentrations in the laboratory (LeChevallier and Au, 2004;Brown and Sobsey, 2010;Basic Water Needs India Pvt Ltd, n. d.-b), and in the field (Mohamed et al, 2015;Clasen et al, 2007;Souter et al, 2003;Ziff, 2008;Brown et al, 2008). Boiling served as a comparison for the HWTS retail products; it has been shown to significantly reduce E. coli in field conditions (Brown and Sobsey, 2012).…”
Section: The Six Hwts Optionsmentioning
confidence: 99%
“…19 Overreporting of HWT in experimental settings is a common phenomenon, [20][21][22][23] and so, it may also be prevalent outside this context. Second, as depicted in Figure 1, HWT is a complex behavior, often performed as a batch process where small batches of drinking water are treated at a time, on a daily or otherwise frequent basis, 24 and requires the user to remain motivated and committed to integrate the practice in their daily routines. As shown by several quantitative microbial risk assessment models, the effectiveness as well as the consistency of its use (also referred to in the literature as adherence or compliance) are the key aspects to ensure the protective effects of HWT.…”
Section: Introductionmentioning
confidence: 99%